SISTEM INFORMASI PELACAKAN DATA ALUMNI JURUSAN MANAJEMEN INFORMATIKA IAIN BATUSANGKAR BERBASIS WEB - Rahmi, Lidya; Septiana, Trisya; Marlion, Farid Ahmad; Hidayat, Rahmat (IAIN Batusangkar, 2019)
Improving the quality of services for students from the Batusangkar IAIN Information Management Department requires a system that can provide information needed by students and graduates such as information about alumni data and alumni careers themselves. In addition, this system can also be used as a means to establish communication and manage friendship between students and alumni. This research was carried out in several stages, namely: Collecting data through field studies by observing and observing the IAIN Batusangkar's Information Management Study Program, developing the system using the waterfall method and proceeding with the process, database and interface design. One indicator of the success of the education process can be seen from the success of alumni both continuing studies at a higher level, as well as various fields of work carried out professionally, but the Department of Information Management has not been managed and organized systematically causing some alumni data to not be captured properly, resulting in the lack of information and communication between alumni and alumni. The results of this study are in the form of developing a tracking information system for alumni that contains the amount of alumni data that has worked, alumni workplaces. For this reason, it is necessary to create a system to facilitate the institution, especially the informatics management department in tracking alumni. In this research the web-based application system is designed using supporting applications such as Apache, MySQL and Macromedia Dream Weaver and the waterfall modeling method.